2014
DOI: 10.5194/acp-14-3479-2014
|View full text |Cite
|
Sign up to set email alerts
|

Trend and variability in ozone in the tropical lower stratosphere over 2.5 solar cycles observed by SAGE II and OSIRIS

Abstract: Abstract.We have extended the satellite-based ozone anomaly time series to the present (December 2012) by merging SAGE II (Stratospheric Aerosol and Gas Experiment II) with OSIRIS (Optical Spectrograph and Infrared Imager System) and correcting for the small bias (∼ 0.5%) between them, determined using their temporal overlap of 4 years. Analysis of the merged data set shows a statistically significant negative trend at all altitudes in the 18-25 km range, including a trend of (−4.6 ± 2.6) % decade −1 at 19.5 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 52 publications
11
52
0
Order By: Relevance
“…The decreasing trend is higher in the lower stratosphere, and its magnitude decreases with altitude. Sioris et al (2014) also reported a significant decreasing trend in ozone in the lower stratosphere (18.5-24.5 km) during 1984 to 2012 from merged satellite data of SAGE II and OSIRIS over a latitude bin 7.5 • N-7.5 • S. In our analysis the ozone trend becomes positive over Trivandrum and New Delhi between 22.5 and 30 km, and the positive trend is higher over Trivandrum than New Delhi. The positive trend in ozone is significant over Trivandrum and it is only significant around 27 km over New Delhi.…”
Section: Long-term Trendssupporting
confidence: 48%
“…The decreasing trend is higher in the lower stratosphere, and its magnitude decreases with altitude. Sioris et al (2014) also reported a significant decreasing trend in ozone in the lower stratosphere (18.5-24.5 km) during 1984 to 2012 from merged satellite data of SAGE II and OSIRIS over a latitude bin 7.5 • N-7.5 • S. In our analysis the ozone trend becomes positive over Trivandrum and New Delhi between 22.5 and 30 km, and the positive trend is higher over Trivandrum than New Delhi. The positive trend in ozone is significant over Trivandrum and it is only significant around 27 km over New Delhi.…”
Section: Long-term Trendssupporting
confidence: 48%
“…Note that because the latitudinal coverage varies throughout the year due to the sun-synchronous ter-minator orbit, the daily average RSAS pointing correction can manifest with meridional structure even though latitudinal dependence is averaged over any given day. The decreasing trend in the tropical lower stratosphere, found previously by Sioris et al (2014) and Bourassa et al (2014), remains statistically significant in these updated and pointing-corrected results, although with slightly reduced extent. The trend results are very consistent with those presented by Steinbrecht et al (2017) and Sofieva et al (2017), which also use this drift-corrected OSIRIS data in combination with SAGE II, OMPS, and other limb data records.…”
Section: Impact On Trendsmentioning
confidence: 49%
“…The original ozone trend work using the Odin-OSIRIS (Optical Spectrograph and Infrared Imager System) instrument (Murtagh et al, 2002;Llewellyn et al, 2004;McLinden et al, 2012) ozone data was performed by Sioris et al (2014) and focused only on the tropical lower stratosphere. This was extended by Bourassa et al (2014) to cover altitudes from 18 to 50 km over the latitude range 60 • S to 60 • N. Both of these studies performed a merging of the OSIRIS version 5.07 ozone data product, from 2002 to 2013, with the version 7 solar occultation profiles obtained by the Stratospheric Aerosol and Gas (SAGE) II satellite instrument, which extend over 1984-2005(McCormick et al, 1989Damadeo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The merging is performed on deseasonalized anomalies computed from each individual dataset. This method is often used for creating long-term data records (e.g., IPCC, 2013;WMO, 2014), as well as for trend analyses of ozone (e.g., Bourassa et al, 2014;Randel and Thompson, 2011;Sioris et al, 2014;Steinbrecht et al, 2017), stratospheric temperature (Randel et al, 2009;Seidel et al, 2011;Thompson et al, 2012) and water vapor (Jones et al, 2009). The main advantage of using deseasonalized anomalies is that biases due to different sampling patterns (including the difference in local time) and instrumental biases are automatically removed, if the sampling patterns do not change over time.…”
Section: Introductionmentioning
confidence: 99%